Neuromuscular Stimulation as an Intervention Tool for Recovery from Upper Limb Paresis after Stroke and the Neural Basis - Shigeru Obayashi; Hirotaka Saito (Applied Sciences, 2022)
Neuromodulators at the periphery, such as neuromuscular electrical stimulation (NMES), have been developed as add-on tools to regain upper extremity (UE) paresis after stroke, but this recovery has often been limited. To overcome these limits, novel strategies to enhance neural reorganization and functional recovery are needed. This review aims to discuss possible strategies for enhancing the benefits of NMES. To date, NMES studies have involved some therapeutic concerns that have been addressed under various conditions, such as the time of post-stroke and stroke severity and/or with heterogeneous stimulation parameters, such as target muscles, doses or durations of treatment and outcome measures. We began by identifying factors sensitive to NMES benefits among heterogeneous conditions and parameters, based on the “progress rate (PR)”, defined as the gains in UE function scores per intervention duration. Our analysis disclosed that the benefits might be affected by the target muscles, stroke severity and time period after stroke. Likewise, repetitive peripheral neuromuscular magnetic stimulation (rPMS) is expected to facilitate motor recovery, as already demonstrated by a successful study. In parallel, our efforts should be devoted to further understanding the precise neural mechanism of how neuromodulators make UE function recovery occur, thereby leading to overcoming the limits. In this study, we discuss the possible neural mechanisms.